1992
DOI: 10.1016/0038-1098(92)90577-v
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced shift of the photoluminescence band in single crystals of buckminster fullerene C60 and its implications for superconductivity in doped samples

Abstract: W o roport tho firat obsorvation of a largo prmaauro-inducod rod-ahift of tho photolu~inosconco b8nd in singlo cryatala of C60 and tho associatod colour chango of tho sup10 from rod to black at-3.2 QPa. Intorproting thm rod ahift of tho l\ukroaconco band aa 8 roduction of tho bandgap E of tho cqatal, wm got tho proaauro dorivativo ap =-0.138 OV/w8. %ia roault

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 15 publications
3
7
0
Order By: Relevance
“…When the pressures are higher than 5.57 GPa, the broad PL spectra of C 60 nanotubes disappear. The redshift of PL spectra indicate that the band gap of C 60 reduced with pressure increasing, which suggest that the interaction of C 60 molecules were enhanced because of the effect of pressure, in agreement with the previous results on both C 60 and C 70 …”
Section: Resultssupporting
confidence: 91%
“…When the pressures are higher than 5.57 GPa, the broad PL spectra of C 60 nanotubes disappear. The redshift of PL spectra indicate that the band gap of C 60 reduced with pressure increasing, which suggest that the interaction of C 60 molecules were enhanced because of the effect of pressure, in agreement with the previous results on both C 60 and C 70 …”
Section: Resultssupporting
confidence: 91%
“…Under ambient conditions, we observe two bands, centered at 1.67 and 1.58 eV. These values are in reasonably good agreement with 1.66 and 1.52 eV observed for pristine and photopolymerized and pressure-synthesized samples, respectively, [8,[11][12][13][14]. The pressure dependences of the mean energy (identified with the electronic energy band gap, E g ), relative intensity and FWHM of the two bands resolved in these spectra are shown in Fig.…”
Section: Photoluminescence Spectrasupporting
confidence: 87%
“…High pressure studies on fullerenes have addressed three issues: (i) the pressure dependence of the orientational ordering transition temperature [22], (ii) the effect on the bandgap E g related to the highest occupied molecular orbital (HOMO) ± ± lowest unoccupied molecular orbital (LUMO) gap [11,23], and (iii) the nature of the high pressure phases. Photoluminescence [23] and optical reflectivity [24] measurements have yielded dE g /dP = ± ± 0.14 eV/GPa for solid C 60 .…”
Section: Pressure Effects On Fullerenes ± ± C 60 and C 70mentioning
confidence: 99%
“…Photoluminescence [23] and optical reflectivity [24] measurements have yielded dE g /dP = ± ± 0.14 eV/GPa for solid C 60 . Under static hydrostatic pressures at room temperature, Raman and optical reflectivity studies have revealed that C 60 transforms completely to the amorphous carbon phase around 22 GPa which is irreversible on release of pressure [21].…”
Section: Pressure Effects On Fullerenes ± ± C 60 and C 70mentioning
confidence: 99%
See 1 more Smart Citation